Recovery process of patients with iliac vein compression syndrome after stenting: a grounded theory study - Yi-Yun Zeng; Wen-Ling Chen; Jimmy Wei Hwa Tan; Shih-Chun Lin; Kuan-Yi Yen; Fan-Hao Chou; Peta-Anne Zimmerman (BMC Cardiovascular Disorders)
Abstract Background Iliac vein compression syndrome (IVCS) impedes venous blood return from the lower extremities due to iliac vein compression, manifesting as leg swelling, varicose veins, and thrombosis. These symptoms significantly degrade quality of life. Although iliac vein stenting provides symptomatic relief, the recovery process is protracted and fraught with challenges such as in-stent restenosis and psychological distress. This study aims to deepen our understanding of patient coping strategies by exploring the entire journey from diagnosis through stenting to recovery in individuals affected by IVCS. Methods This qualitative study employed a grounded theory approach, conducting in-depth, semi-structured interviews with 16 patients who had undergone stenting for IVCS. Participants were recruited from a teaching hospital in Taiwan and interviewed between August 2022 and July 2023. Results The recovery process for the patients involved five stages and 11 subcategories, which outlined a journey toward a new direction of health. The stages were (1) exacerbation—worsening symptoms that disrupt daily life, compelling the patient to finally address the issue; (2) seeking help—medical professional help sought; (3) despondency—ongoing pain and recurring symptoms after surgery; (4) adjustment—self-directed health promotion with support systems aiding in recovery; and (5) health preservation—suitable health care and beneficial exercise habit development. Conclusions The recovery process was depicted in a linear diagram of living with a new direction for health. Careful attention should be paid to the importance of clarifying patient expectations after stenting, addressing post-treatment physical discomfort and emotional anxiety issues, and enabling patients to confidently undergo follow-up and rehabilitation to achieve their recovery goals. Clinical trial number Not applicable.